LITERATURE REVIEW: KUALITAS UDARA DALAM RUANG SEBAGAI FAKTOR RISIKO KEJADIAN SICK BUILDING SYNDROME - Oktavia, Widya Ayu; Setiani, Onny; Joko, Tri; Sulistiyani, Sulistiyani; Suhartono, Suhartono (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Indoor air quality is a crucial aspect of creating a healthy and productive work environment. Decreased air quality has the potential to cause various health problems in building occupants. One of the health problems that is often associated with poor indoor air quality is Sick Building Syndrome (SBS). This study aims to synthesize findings from various studies to provide a comprehensive understanding of environmental risk factors that contribute to the occurrence of SBS. This study is a literature review to review the results of previous studies related to indoor air quality and sick building syndrome. The search database used in searching for this article comes from national and international journals. The selection of articles is based on inclusion criteria, including publication within the last 10 years, a cross-sectional study design, and discussion of indoor air quality in relation to the occurrence of SBS. The results of the review of 10 articles showed that the factors that trigger the onset of sick building syndrome symptoms include temperature, humidity, lighting, particulates (PM2.5 and PM10), air flow rate, ventilation systems, and exposure to chemical contaminants. Environmental management as an effort to overcome the occurrence of sick building syndrome includes improving the ventilation system, controlling temperature and humidity, managing chemical contaminants, controlling particulates, and improving lighting. SBS symptoms are influenced by several environmental factors that can affect worker health and productivity. Therefore, environmental management is needed as a way to overcome the occurrence of SBS.